Bacterial Dormancy Is More Prevalent in Freshwater than Hypersaline Lakes - Aanderud, Zachary T.; Vert, Joshua C.; Lennon, Jay T.; Magnusson, Tylan W.; Breakwell, Donald P.; Harker, Alan R. (Frontiers in Microbiology, 2016)
Bacteria employ a diverse array of strategies to survive under extreme environmental conditions but maintaining these adaptations comes at an energetic cost. If energy reserves drop too low, extremophiles may enter a dormant state to persist. We estimated bacterial dormancy and identified the environmental variables influencing our activity proxy in ten hypersaline and freshwater lakes across the Western United States. Using ribosomal RNA:DNA ratios as an indicator for bacterial activity, we found that the proportion of the community exhibiting dormancy was 16% lower in hypersaline than freshwater lakes. Based on our indicator variable multiple regression results, saltier conditions in both freshwater and hypersaline lakes increased activity, suggesting that salinity was a robust environmental filter structuring bacterial activity in lake ecosystems. To a lesser degree, higher total phosphorus concentrations reduced dormancy in all lakes. Thus, even under extreme conditions, the competition for resources exerted pressure on activity. Within the compositionally distinct and less diverse hypersaline communities, abundant taxa were disproportionately active and localized in families Microbacteriaceae (Actinobacteria), Nitriliruptoraceae (Actinobacteria), and Rhodobacteraceae (Alphaproteobacteria). Our results are consistent with the view that hypersaline communities are able to capitalize on a seemingly more extreme, yet highly selective, set of conditions and finds that extremophiles may need dormancy less often to thrive and survive.